PENYEBAB TERJADINYA TINDAKAN MAIN HAKIM SENDIRI ATAU EIGENRICHTING YANG MENGAKIBATKAN KEMATIAN (CONTOH KASUS PEMBAKARAN PELAKU PENCURIAN MOTOR DENGAN KEKERASAN DI PONDOK AREN TANGERANG) - Chandro Panjaitan; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
Cases of vigilante action are committed by a group of persons are not justified in the law. Those are cases which is unlawful, immoral, irresponsible and does not have an attitude that respects the law.Vigilante cases should have been reported to the authorities and the perpetrator should be punished in accordance to the existing law and regulations. There is no apparent regulations regarding the act of vigilante, instead there are some articles in Indonesian’s Criminal Code which can be used against the perpetrators. In this case Article 170 and 351 of Indonesian’s Criminal Code somehow has been used to deal with vigilante cases. It is important to learn what are the factors of the vigilante case in PondokAren, Tangerang which will be the main research in this thesis and also the prevention that should be done in order to avoid the same incident in the future. The research data shows that the factors behind perpetrators being vigilante is based on emotional factors, the lack of trust in the law and situation factor. On the other hand to prevent further case in the future the authorities need to improve their work from several aspects. Thus, creating a positive opinion on public.